Should oncoplastic breast conserving surgery be used for the treatment of early stage breast cancer? Using the GRADE approach for development of clinical recommendations. (June 2021) - Rocco, Nicola; Catanuto, Giuseppe; Cinquini, Michela; Audretsch, Werner; Benson, John; Criscitiello, Carmen; Di Micco, Rosa; Kovacs, Tibor; Kuerer, Henry; Lozza, Laura; Montagna, Giacomo; Moschetti, Ivan; et al.
Abstract: Introduction: The potential advantages of oncoplastic breast conserving surgery (BCS) have not been validated in robust studies that constitute high levels of evidence, despite oncoplastic techniques being widely adopted around the globe. There is hence the need to define the precise role of oncoplastic BCS in the treatment of early breast cancer, with consensual recommendations for clinical practice. Methods: A panel of world-renowned breast specialists was convened to evaluate evidence, express personal viewpoints and establish recommendations for the use of oncoplastic BCS as primary treatment of unifocal early stage breast cancers using the GRADE approach. Results: According to the results of the systematic review of literature, the panelists were asked to comment on the recommendation for use of oncoplastic BCS for treatment of operable breast cancer that is suitable for breast conserving surgery, with the GRADE approach. Based on the voting outcome, the following recommendation emerged as a consensus statement: Oncoplastic breast conserving surgery should be recommended versus standard breast conserving surgery for the treatment of operable breast cancer in adult women who are suitable candidates for breast conserving surgery (with very low certainty of evidence). Discussion: This review has revealed a low level of evidence for most of the important outcomes in oncoplastic surgery with lack of any randomized data and absence of standard tools for evaluation of clinical outcomes and especially patients' values. Despite areas of controversy, about one-third (36%) of panel members expressed a strong recommendation in support of oncoplastic BCS. Presumably, this reflects a synthesis of views on the relative complexity of these techniques, associated complications, impact on quality of life and costs.